2019
DOI: 10.1177/0271678x19867980
|View full text |Cite
|
Sign up to set email alerts
|

Modeling hyperosmotic blood–brain barrier opening within human tissue-engineered in vitro brain microvessels

Abstract: As the majority of therapeutic agents do not cross the blood–brain barrier (BBB), transient BBB opening (BBBO) is one strategy to enable delivery into the brain for effective treatment of CNS disease. Intra-arterial infusion of the hyperosmotic agent mannitol reversibly opens the BBB; however, widespread clinical use has been limited due to the variability in outcomes. The current model for mannitol-induced BBBO assumes a transient but homogeneous increase in permeability; however, the details are poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 57 publications
4
41
2
Order By: Relevance
“…Others expanded on the use of perfusable microfluidics to study the BBB, focusing on the role of plasma in electrolyte balance and in particular the use of hyperosmotic therapies for the treatment of central nervous system disease. Linville et al [56], using stem cell-derived brain Once the microchannels are created using these top-down approaches they are then endothelialized. In order to accomplish this an ECM protein, such as collagen, fibronectin or laminin is infused and allowed to adsorb to the channels inner surface [46][47][48].…”
Section: Plasma-endothelium Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Others expanded on the use of perfusable microfluidics to study the BBB, focusing on the role of plasma in electrolyte balance and in particular the use of hyperosmotic therapies for the treatment of central nervous system disease. Linville et al [56], using stem cell-derived brain Once the microchannels are created using these top-down approaches they are then endothelialized. In order to accomplish this an ECM protein, such as collagen, fibronectin or laminin is infused and allowed to adsorb to the channels inner surface [46][47][48].…”
Section: Plasma-endothelium Interfacementioning
confidence: 99%
“…Others expanded on the use of perfusable microfluidics to study the BBB, focusing on the role of plasma in electrolyte balance and in particular the use of hyperosmotic therapies for the treatment of central nervous system disease. Linville et al [56], using stem cell-derived brain microvascular ECs in a PDMS-based model, demonstrated that mannitol, an osmotic diuretic used clinically to treat elevated intracranial pressure, resulted in a dose-dependent, spatially heterogenous increase in paracellular permeability by forming transient focal leaks in the vascular endothelium. In addition, using bFGF before treatment with mannitol, they were able to demonstrate its direct role in the modulation of the degree of BBB opening and subsequent recovery.…”
Section: Plasma-endothelium Interfacementioning
confidence: 99%
“…Cleaved‐IL1β and cleaved‐IL18 released from inflammasome‐forming cells induce production of proinflammatory factors by neighbor cells, including IFNγ, TNFα, and ROS . The proinflammatory factors further impair blood‐brain barrier (BBB) and attract peripheral leukocytes . Besides, pyroptosis induced by inflammasome activation gives rise to DAMPs, which activate inflammasome and exacerbate the inflammatory status.…”
Section: Inflammasome Is An Amplifier Of Neural Inflammationmentioning
confidence: 99%
“…21 The proinflammatory factors further impair blood-brain barrier (BBB) and attract peripheral leukocytes. 22,23 Besides, pyroptosis induced by inflammasome activation gives rise to DAMPs, which activate inflammasome and exacerbate the inflammatory status. Neural inflammation plays a key role in multiple aging-related neurological diseases.…”
mentioning
confidence: 99%
“…Importantly, our hierarchical model allows probing of how BBB phenotype changes across the vascular tree. Recently, we demonstrated use of BBB microvessels for studying hyperosmotic BBB disruption [71], but do not know if capillaries are more susceptibility to opening. Figure 1 dhBMECs were differentiated from the WTC iPSC line with a fluorescently-tagged plasma membrane (Fig.…”
Section: Engineering Bbb Hierarchymentioning
confidence: 99%